What is Qualitative Interviewing? - Janet Holland; Rosalind Edwards (Bloomsbury Academic, 2013)
With short accessibly written chapters, What is Qualitative Interviewing? explores a range of interview types and practices, and provides illuminating examples with diagrams and extracts.
English